KEBIJAKAN PENGEMBANGAN KARIR PEGAWAI DI BAGIAN UMUM DAN KEPEGAWAIAN DI RSUD PRATAMA - Syamsiar I. Mahmud (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2023)
Career development patterns are assessed based on indicators as explained in Permenpan RB No 22 of 2021 using principles including professionalism and transparency, integrity and fairness. The research objectives are: 1). Employee career development policies in general and staffing departments at Pratama Hospital, reviewed from: a). ASN Competency Standards, b). Discipline Development, c). Competency Development and Career Development, d). Years of service. The research method used is descriptive qualitative, the research location is at Pratama Hospital. Data collection techniques were in the form of observation, interviews and documentation which were then analyzed using qualitative data based on Miles and Huberman's concepts. The research results show that: 1). Employee career development policies in general and staffing departments at Pratama Hospital, reviewed from: a). ASN Competency Standards, b). Discipline Development, c). Competency Development and Career Development, d). Working Period, e). Employee Profile has been implemented but not optimal. ASN competency standards in the aspects of technical and socio-cultural competence have not been implemented optimally because not all employees have the opportunity to attend training and there are still sectoral egos between each individual. Furthermore, the aspects of competency development and employee career development have not been optimal. non-optimal education and training attended by employees cannot be interpreted in every task. In addition, in the aspect of the employee profile of employees in the General